Under Our Eye: Margaret Atwood’s Variation on the Panopticon in The Heart Goes Last - Kuźnicki, Sławomir (Zagadnienia Rodzajów Literackich, 2020)
In her dystopian dark comedy The Heart Goes Last (2015), Margaret Atwood openly refers to Jeremy Bentham’s concept of the Panopticon. The future world depicted in her novel is filled with violence and deprived of both human bonds and hope. Hence, being contained, monitored and — after Foucault — disciplined and punished appears to be the characters’ last resort. Surveillance tempts both sexes as it is politically correct and universal, and it does not privilege one group of people over the other. The article discusses the dystopian vision of the near future as created by Atwood in her 2015 novel, with direct references to the conception of the Panopticon, both in its original meaning proposed by Bentham, and — more significantly — in Michel Foucault’s reading of this idea as a metaphor of the way western societies are organized.